Expressing Nursing as Caring through Music - Locsin, Rozzano C. (Silliman Journal, 2023)
Music illuminates the profession of nursing which is the lived experince shared between the nurse and the person being nursed. To describe this, two creative and imaginative applications of music are illustrated: as an embodiment and as complement to the nursing situation. Music both as an artform and as a therapeutic medium is described and illustrated to contrast way of expressing the experience of caring in nursing.